A study on the mean value of the distance between the incisive papilla and the upper central incisors among 37 U.P. Manila College of Dentistry Students - Lucas, Lallaine B.
The mean values for the (distance between the incisive papilla and the maxillary central incisors were obtained by measuring photocopied casts of 37 U.P. College of Dentistry students. The values were subjected to statistical analysis using the T-test and Z-test on mean. It was discovered that the acceptable range for this sample population was incomparable to the standard value, 8-10 mm which is based on Caucasian norm.